AB1227-HPR Validation and applicability of a novel osteomalacia knowledge based educational instrument (OKQ). (15th June 2017) - Robinson, S; Waxman, R; Walker, D; Helliwell, P; Adebajo, A
Abstract : Background: Osteomalacia is caused by a deficiency of vitamin D and can be corrected by changes in diet, lifestyle and supplementation. Consequently, it is a condition where education has a primary role in prevention. Objectives: If educational interventions are to be developed and evaluated, then an instrument for measuring knowledge is required. This has led us to develop a novel Osteomalacia Knowledge Questionnaire (OKQ). Methods: Based on nominal group technique, a steering group of people who are knowledgeable about osteomalacia, educational theory and questionnaire development was convened. The group decided to use true and false questions. Important areas of knowledge of osteomalacia were first determined by the group and then relevant statements which were true or false were written and grouped into 8 sections of 5 questions, each covering the different areas of knowledge. This resulted in a knowledge instrument with 40 questions in all. The questions were tested for utility and ambiguity in the group and modified and replaced accordingly. The questionnaire was then trialled in 37 people of South Asian origin (an osteomalacia susceptible population), in three groups. Participants were initially administered the OKQ and then received an educational intervention comprising a practitioner led education session on osteomalacia, including a presentation and written or electronic material. Participants were re tested with the OKQ after 6 weeks. Although there is no "gold standard" for measuring knowledge about osteomalacia, if effective, increased knowledge should lead to an increase in vitamin D (Vit D) levels and a decrease in parathormone (Pth) levels. Vitamin D and Parathormone levels were measured alongside the OKQ in 2 of the groups before and after the educational intervention Results: Baseline knowledge about osteomalacia was low pre education averaging only 12.7 out of 40 (range 0–29) (n=37). A total of 30 participants (81%) attended for the follow up test. They averaged a score of 13.9 at baseline and 23.4 at follow up. This was statistically significant (p=0.002 Mann Whitney) and demonstrated sensitivity to change of the OKQ. Knowledge at baseline was correlated with vit D and Pth blood levels for two of the groups (n=27). This showed correlation coeficients of 0.128 and -0.407 respectively. For change of knowledge and change of parathormone (n=21) the r value was -0.324 suggesting a relationship between knowledge and Pth that is worthy of confirmation through further studies. Conclusions: A novel questionnaire has been developed that has face validity for testing knowledge about osteomalacia. It has proved feasible and shown sensitivity to change. It has also shown promising correlation with biochemical measures of osteomalacia. Acknowledgements: This study was funded by Arthritis Research United Kingdom. Disclosure of Interest: None declared